Development of an anti-microbial peptide-mediated liposomal delivery system: a novel approach towards pH-responsive anti-microbial peptides. (3rd May 2016) - Zhang, Qianyu; Tang, Jie; Ran, Rui; Liu, Yayuan; Zhang, Zhirong; Gao, Huile; He, Qin
Abstract: On one hand, the application of anti-microbial peptides (AMPs) in the construction of AMPs-mediated drug delivery system has not yet been fully exploited; on the other hand, its non-selectivity in vivo has also limited its clinical application. In this work, we chose one pH-responsive peptide, [D]-H6 L9, and functionalized it onto the surface of liposomes (D-Lip). The protonation of histidines in the sequence of [D]-H6 L9 under pH 6.3 could switch the surface charge of D-Lip from negative (under pH 7.4) to positive (under pH 6.3), and the cellular uptake and tumor spheroids uptake were increased accordingly. Lysosome co-localization assay suggested that there was only little overlap of D-Lip with lysosomes in 12 h, which indicated that D-Lip could escape lysosomes effectively. In vivo biodistribution assay on C26 tumor-bearing BALB/C mice showed that DiR-labeled D-Lip could reach tumors as much as PEG-Lip, and both tumor slices and quantitative measurement of dispersed cells of in vivo tumors by flow cytometry demonstrated that D-Lip could be taken up by tumors more efficiently. Therefore, we have established an anti-microbial peptide-mediated liposomal delivery system for tumor delivery.